Community multiculturalism and immigrant crime - Leerkes, Arjen (European journal of criminology, 2023)
There is considerable international and local-level variation in immigrant crime. In this article, we propose a theoretical model to better understand that contextual variation. Furthermore, we present the results of our first attempts to empirically assess the validity of the framework, focussing on local-level variation in crime among residents of Turkish or Moroccan origin in the Netherlands. The proposed model connects Berry's acculturation theory to criminological theories, using relevant findings from the immigration acculturation literature as starting points. It theorises that host societies with a ?multicultural acculturation orientation? tend to reduce immigrant crime by fostering informal social control and attenuating criminogenic strains. The empirical analyses explore whether local-level variation in multicultural attitudes among the native-Dutch indeed predicts municipal variation in the number of registered suspected crimes among first- and second-generation immigrants, focussing on men of Turkish or Moroccan origin residing in 35 Dutch cities. The empirical analyses are based on a unique database that combines aggregated survey data, which were used to measure natives? acculturation attitudes, with administrative microdata, including micro-level police data. Evidence is found for a protective effect of local-level multiculturalism for first-generation immigrant crime in particular, especially for immigrant men living in larger local immigrant communities. We also find stronger effects for the more cohesive and societally accepted Turkish-Dutch group than for the more fragmented and excluded Moroccan-Dutch.